A unique case of acute brain haemorrhage with left ventricular systolic failure requiring ECMO - Kristy Xinghan Fu; Beatrice Hui Zhi Ng; Melissa Hui Xin Chua (BMC, 2019)
Abstract Background Acute left ventricular (LV) systolic failure as a consequence of acute severe brain injury with status epilepticus in a young infant is not common; managing such a patient on extracorporeal membrane oxygenation (ECMO), which requires proper anticoagulation adds further substrate to a particularly intriguing and novel case worthy of reporting. Takotsubo syndrome and its peculiar clinical presentation is not commonly reported in the paediatric population, yet the high likelihood of this diagnosis joining the dots up for this case invites our curiosity and reflection through the clinical management of this case. Case presentation A previously healthy 9-month-old local Chinese boy presented with generalised seizures secondary to acute severe brain injury, with signs of sympathetic overdrive, followed by rapidly progressive cardiogenic shock and respiratory failure, eventually requiring ECMO support. Neuroimaging at presentation revealed bilateral subdural haemorrhages. His cardiac function recovered within the next 24 h revealing the reversibility nature of Takotsubo cardiomyopathy. Conclusions This is a captivating case depicting a series of unfortunate and unpredictable clinical events occurring in a previously well infant, which at initial presentation challenged the managing team with regards to its exact aetiology of acute brain injury and acute cardiorespiratory failure. Consideration of various differential diagnoses and finally narrowing down to that of stress-induced reversible cardiomyopathy (Takotsubo syndrome) following his intracranial bleed, versus that of coexisting dual pathology - acute brain injury with concomitant acute viral myocarditis, deepened our understanding of the pathophysiology of each disease process, and how it possibly interlinks between different organ systems.